2006
DOI: 10.1089/dna.2006.25.429
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Transfer of a Growth Hormone-Releasing Hormone Peptide from Mother to Fetus in the Rat

Abstract: Previous studies showed that when growth hormone-releasing hormone (GHRH) was administered to either pregnant rats or pigs as a plasmid-mediated therapy, pituitary weight, somatotroph and lactotroph numbers, and postnatal growth rate of the offspring increased. To determine if these responses resulted from direct effects of GHRH on the fetus or were secondary to effects incurred in the mother, we studied in the rat the transplacental transfer of a GHRH analog (HV-GHRH) to the fetus from the maternal circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…For instance, gilts treated in the last part of gestation with a HV-GHRHexpressing plasmid had heavier piglets, and the offspring's postnatal growth rate and welfare was enhanced. Changes in pituitary cell lineage in the offspring of treated pregnant sows and rats have been shown, with higher numbers of GH and PRL-producing cells, which can then directly impact their growth and welfare once the postnatal growth comes under the control of GH and IGF-I (Khan et al, 2003;Fiorotto et al, 2006). The increased growth in offspring is not due to maternal pregnancy diabetes (glucose and insulin were normal in all studies, including this one).…”
mentioning
confidence: 60%
“…For instance, gilts treated in the last part of gestation with a HV-GHRHexpressing plasmid had heavier piglets, and the offspring's postnatal growth rate and welfare was enhanced. Changes in pituitary cell lineage in the offspring of treated pregnant sows and rats have been shown, with higher numbers of GH and PRL-producing cells, which can then directly impact their growth and welfare once the postnatal growth comes under the control of GH and IGF-I (Khan et al, 2003;Fiorotto et al, 2006). The increased growth in offspring is not due to maternal pregnancy diabetes (glucose and insulin were normal in all studies, including this one).…”
mentioning
confidence: 60%
“…Also importantly, no adverse maternal effects were reported in these studies of GHRH-transduced dams studied throughout the three pregnancies following GHRH plasmid incorporation (Person et al 2008). The variant form of human GHRH, used to electroporate sows in the studies described above, crosses the rat placenta (Fiorotto et al 2006), while circulating GHRH is elevated at birth in progeny of GHRH-plasmid-treated pigs (Khan et al 2003), and circulating IGF1 is elevated in progeny of GHRH-plasmid-treated rats (Khan et al 2002). Effects of elevated maternal GHRH are therefore likely to reflect direct effects on the developing fetus in addition to effects on the maternal GH axis.…”
Section: Strategies To Increase Maternal Ghmentioning
confidence: 91%
“…32 Fioretto et al found a transplacental transfer of a GHRH analog from mother to fetus in the rat. 33 Based on these studies, an effect of GHRH antagonists on a fetus cannot be excluded and therefore pregnancy is contraindicated during therapy with these compounds. However, given the rather short half-life of GHRH antagonists, pregnancy can be planned directly after stopping the treatment.…”
Section: Discussionmentioning
confidence: 99%